Digging up Trenches: Populism, Selective Mobility, and the Political Polarization of Italian Municipalities - Luca Bellodi; Frédéric Docquier; Stefano Iandolo; Massimo Morelli; Riccardo Turati (Institute of Labor Economics (IZA), 2024)
We study the effect of local exposure to populism on net population movements by citizenship status, gender, age and education level in the context of Italian municipalities. We present two research designs to estimate the causal effect of populist attitudes and politics. Initially, we use a combination of collective memory and trigger variables as an instrument for the variation in populist vote shares across national elections. Subsequently, we apply a regression discontinuity design to estimate the effect of electing a populist mayor on population movements. We establish three converging findings. First, the exposure to both populist attitudes and policies, as manifested by the vote share of populist parties in national election or the closeelection of a new populist mayor, reduces the attractiveness of municipalities, leading to larger population outflows. Second, the effect is particularly pronounced among young, female, and highly educated natives, who tend to relocate across Italian municipalities rather than internationally. Third, we do not find any effect on the foreign population. Our results highlight a foot-voting mechanism that may contribute to a political polarization in Italian municipalities.
Keywords: D72; F22; F52; J61; 330; migration; human capital; populism; Italian politics